2007
DOI: 10.1111/j.1440-1584.2007.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute rheumatic fever: Adherence to secondary prophylaxis and follow up of Indigenous patients in the Katherine region of the Northern Territory

Abstract: Within this population adherence with penicillin prophylaxis is inadequate to protect against recurrence of ARF and consequent worsening of rheumatic heart disease. In addition, the Rheumatic Fever Registry Guidelines for specialist follow up and echocardiogram are not being adhered to for many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 17 publications
2
33
2
1
Order By: Relevance
“…[1][2][3][4] The compliance to different prophylactic regimens is relatively poor. 9,10 Azithromycin, with a long half-life, which can be administered once weekly was thought to improve the compliance. 14 So we decided to study the effectiveness of AZT in the secondary prophylaxis of rheumatic fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The compliance to different prophylactic regimens is relatively poor. 9,10 Azithromycin, with a long half-life, which can be administered once weekly was thought to improve the compliance. 14 So we decided to study the effectiveness of AZT in the secondary prophylaxis of rheumatic fever.…”
Section: Discussionmentioning
confidence: 99%
“…8 The main problem with the different regimens of secondary prophylaxis is compliance. 9,10 So, we are on the look-out for safer alternatives with improved patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Initiatives are being introduced to improve specialist care for Indigenous Australians with chronic diseases, including new programs to support primary care providers to better coordinate chronic disease management, and increase access to specialist and multidisciplinary team care. A recent study of patients with RHD living in five communities around Katherine in the Northern Territory found that around two-thirds of patients were receiving ongoing secondary preventive treatment in accordance with guidelines: 56% of patients received prophylactic penicillin injections; 63% received echocardiograms and 59% had a specialist review (Stewart et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the registry will serve as an epidemiological tool for gathering detailed echocardiography information for the purpose of research, compiling reference ranges and guiding the development of protocols and guidelines to improve secondary prophylaxis adherence. (23) It is envisaged that the model of surveillance and prevention of RF/RHD will be successfully established, and can be rolled out at country level in order to prevent RF among children and thus avoid RHD and cardiac surgery. Through efforts such as ASAP as well as implementation of the National Department of Health guidelines for the prevention and treatment of RF/RHD, it is certainly feasible that both RF and RHD could be eradicated from South Africa within one or two generations, mimicking the achievements made recently in Cuba.…”
Section: Launch Of South African Demonstration Sitementioning
confidence: 99%